Integration of a concurrent signature monitoring mechanism in a system-on-a-chip - Kakarountas, Athanasios P.; Goutis, Costas E.; Michail, Harris (My University, 2007)
In this work, an IP infrastructure is presented that provides concurrent signature monitoring to the designed System-on-a-Chip (SoC). Such mechanisms ensure application code consistency and research focus integration inside high performance processor cores. A low-cost but very effective approach is offered, which has been successfully integrated in a prototype targeting safety critical applications. The advantages of the integration of this simple unit in a SoC and its characteristics are also presented. © 2007 IEEE.
Keywords: BIST; Design-for-testability; On-line testing